Analisis pengaruh kafa’ah maliyah dalam mewujudkan keharmonisan keluarga (studi kasus pada Kecamatan Buahbatu Bandung) - Mar’atush Sholihah, Jamilah; Irawan, Deni (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Every married couple aspires to have a harmonious family. However, many face challenges in achieving this, with conflicts such as arguments, differences in opinions, debates, and sometimes leading to divorce. One approach to address these issues is by seeking a compatible partner. Compatibility is considered effective as it aligns with the goals of marriage. Kafa’ah, including economic compatibility (kafa’ah maliyah), is deemed crucial for economic stability and family harmony. This research, conducted in the Buahbatu District, Bandung, aims to analyze the community's perceptions of kafa’ah maliyah and its impact on achieving family harmony. The qualitative case study method revealed diverse perceptions among the Buahbatu community, considering kafa’ah maliyah as vital for realizing family harmony. The influence of kafa’ah maliyah includes reducing financial conflict risks, enhancing cooperation in financial management, improving family stability and well-being, strengthening mutual respect and responsibility, and fortifying emotional bonds between spouses